Physical education curriculum systematizing based on action research: a collaborative network between teacher-researchers from public schools in Quixadá — Ceará, Brazil - Rener Victor Oliveira de Souza; Maurício Teodoro de Souza; Luciano Nascimento Corsino; Willian Lazaretti da Conceição; Carla Ulasowicz; Luciana Venâncio; Luciana Venâncio; Luiz Sanches Neto; Luiz Sanches Neto (Frontiers in Sports and Active Living)
For more than forty years, physical education has been associated with human sciences in Brazil, with an emphasis on the dynamics of culture. This renewing movement challenged the hegemony of sport and health as predominant themes in the school physical education curriculum, as well as pointing out dilemmas to the positivist scientific paradigm. In this sense, advances in theoretical-methodological propositions in Brazilian physical education are intertwined with scientific understandings in the area. Twenty years ago, from a complex epistemological perspective, a curricular systematization—proposed by an autonomous community of teachers-researchers—brought these understandings closer together, valuing the convergence between the dynamics of culture, movement, the body and the environment. In this research, our objective is to analyze how this systematization can contribute to the pedagogical practice of physical education teachers in the public high school network in the city of Quixadá, located in the interior of the state of Ceará, Brazil. Our qualitative itinerary has action research as a method of intervention, including class observations, group meetings and field diary. Data has been analyzed through thematic analysis, characterizing a collaborative network between participants. We identified that curricular documents direct subject content towards the predominance of cultural elements. This direction, in turn, can make it difficult to develop intersubjective knowledge related to the body, movement and the environment. However, when dialoguing with the systematization and reflecting on the curriculum, the thematic subject content blocks make it possible to visualize (inter)personal aspects, movements and environmental demands as complex knowledge specific to physical education.